Radiation dose to the nodal regions during prone versus supine breast irradiation - Csenki M; Újhidy D; Cserháti A; Kahán Z; Varga Z (Dove Medical Press, 2014)
Melinda Csenki, Dóra Újhidy, Adrienn Cserháti, Zsuzsanna Kahán, Zoltán Varga Department of Oncotherapy, University of Szeged, Szeged, Hungary Background: Prone positioning for breast radiotherapy is preferable when the aim is a reduction of the dose to the ipsilateral lung or the heart in certain left-sided cases. Materials and methods: In 100 breast cancer cases awaiting postoperative whole-breast radiotherapy, conformal radiotherapy plans were prospectively generated in both prone and supine positions. The axillary nodal region (levels I–III) and internal mammary (IM) lymph-node region in the upper three intercostal spaces were retrospectively contoured. The mean doses to the nodal regions and the volume receiving 25 Gy (V25Gy), V45Gy, and V47.5Gy were compared between the two treatment positions. Results: In most cases, the doses to axillary levels I–III and the IM lymph nodes were inadequate, regardless of the treatment position. The nodal doses were significantly lower in the prone than in the supine position. The radiation doses to levels II–III and IM nodes were especially low. The V45Gy and V47.5Gy of the level I axillary lymph nodes were 54.6% and 40.2%, respectively, in the supine, and 3.0% and 1.7%, respectively, in the prone position. In the supine position, only 17 patients (17%) received a mean dose of 45 Gy to the axillary level I nodes. Conclusion: The radiation dose to the axillary and IM lymph nodes during breast radiotherapy is therapeutically insufficient in most cases, and is significantly lower in the prone position than in the supine position. Keywords: axillary lymph nodes, breast radiotherapy, internal mammary nodes, prone positioning, supine positioning